2006
DOI: 10.1007/s10561-005-0275-8
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation and Sperm DNA Integrity

Abstract: Cryopreservation of sperm is an extremely important issue in the field of male infertility as freezing can have detrimental effects on a variety of sperm functions, some of them not accessible to the traditional semen quality analysis. In this study, chromatin structure variations in human spermatozoa in semen were studied with the sperm chromatin structure assay (SCSA), both before and after cryopreservation. Samples were divided into two aliquots: the first was analysed without further treatment, while the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 67 publications
5
56
2
2
Order By: Relevance
“…Our study confirmed that DNA fragmentation is increased after cryopreservation as previously described [8,12,42]. However, we also noted that the DNA fragmentation in "swim-up"purified samples is higher following short-term than after longer cryopreservation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study confirmed that DNA fragmentation is increased after cryopreservation as previously described [8,12,42]. However, we also noted that the DNA fragmentation in "swim-up"purified samples is higher following short-term than after longer cryopreservation.…”
Section: Discussionsupporting
confidence: 91%
“…Current cryopreservation protocols involve the freezing of the ejaculate with cryoprotectants which when thawed are "swim-up" purified for use in ART. Previously, it has been described that cryopreservation causes DNA fragmentation in spermatozoa [8,12,42]. In particular, the effect of cryopreservation and thawing on DNA integrity was greater in infertile men than in fertile men [4,12].…”
Section: Introductionmentioning
confidence: 96%
“…This loss in sperm quality is especially significant in patients whose sperm parameters are poor to begin with [Hammadeh et al 1999;McLaughlin et al 1992]. Motility is the most affected parameter [Donnelly et al 2001a;Gandini et al 2006]. O'Connell et al [2002] proposed that the decrease in sperm motility is due to mitochondrial damage and physical changes to the sperm tail.…”
Section: Effects Of Cryopreservationmentioning
confidence: 99%
“…The packaging of DNA in a sperm nucleus follows a long process that begins in spermiogenesis where the histones are replaced by protamines [Boissonneault 2002]. The integrity of spermatozoa seems to be the determining factor in the success of fertilization in both natural and assisted reproductive methods [Gandini et al 2006]. It has been noted that the decrease in post-thaw quality is mostly due to DNA fragmentation that occurs after cryopreservation.…”
Section: Effects Of Cryopreservationmentioning
confidence: 99%
“…All subjects were asked to observe 2-7 days of sexual abstinence prior to sample collection. After semen analysis, semen samples were frozen in liquid nitrogen tanks using a manually controlled freezing procedure as described by Gandini et al (2006) with minor modifications. Briefly, samples were diluted 1 : 1 (v/v) by drop-wise addition of test yolk buffer with glycerol and gentamicin (Irvine Scientific, Santa Ana, CA, USA).…”
Section: Cryopreservation Of Semen Samplesmentioning
confidence: 99%